Swine production simulation model: LIFE SIM - León Velarde, C.U.; Cañas, R.; Osorio, J.; Guerrero, J.; Quiróz, R. (International Potato Center, 2007)
Non-ruminant animals are essential in many resource-poor production systems, particularly in Asia. The feeding strategies are as varied as the different agro ecosystems, thus increasing the challenge faced by researchers and extension agents in the search for appropriate solutions to feeding limitations. Systems analysis provides a unique opportunity to translate existing knowledge into process-based models that can be used to assess year-round feeding strategies at the farm level. Although livestock models have been developed to address similar situations for ruminant animals, swine are seldom included. The present work describes a swine model that analyzes the bioeconomic response to feeding strategies in different production systems. This swine model has been incorporated into the software Livestock Feeding Strategies Simulation Model (LIFE-SIM) complementing the existing models for ruminant species: Dairy, Beef, Goat, and Buffalo (León-Velarde et al., 2006) The model simulates a confined group of animals (at least two females or males) with a weight ranging from 15 to 120 kg, under either an ad libitum or controlled feeding regime with a feed value characterized in terms of dry matter (%), metabolizable energy (ME/kg), crude fiber (%), lysine (%), methionine + cystine (%), threonine (%), and tryptophan (%). The model can store a number of different rations and their prices allowing a comparison during a defined fattening period. Weight gain and the bioeconomic performance of each ration can then be estimated and analyzed.